Effect of rice (Oryza sativa)-establishment methods, tillage practices in wheat (Triticum aestivum) and fertilization on soil physical properties and rice-wheat system productivity on a silty day Mollisol of Uttaranchal - SINGH, Y; BHARDWAJ, A K; SINGH, S P; SINGH, R K; CHAUDHARY, D C; SAXENA, AMAL; SINGH, VIJENDRA; SINGH, SATENDRA PAL; KUMAR, ABNISH (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted for 5 years (1992-93 to 1996-97) to study the effect of crop-establishment methods office (Oryza saliva L.) and wheat (Triticum aestivum L. emend. Fiori & Paol.) and fertilizer rutes on productivity of rice-wheat cropping system. Subsequently on-farm trials were conducted for 3 years (1997-98 to 1999-2000) to compare tillage methods and fertilizer rates. Rice-stablishment methods were transplanting und direct seeding, tillage practices followed in wheat were zero and conventional tillage and 2 fertilizer rates for rice as well as wheat were the recommcnded dose ( 120,26 and 33 kg N, P and K/ha) and 150% of the recommended dose. Performance of transplanted and direct-sceded rice was at par, but in the following season wheat yield was morc in plots where rice was directly seeded. Puddling had adverse effect all following wheat crop. Wheat yields sown with zero tillage was similar to conventional tillage in 3 years, but in 2 years eonventional tillage had advantages in silty clay loam soil when the crop under 2 treatments was sown on the same date. However, in on-farm trials, where zero-till plots were sown earlier than conventional tillage plots, yield in zero till plots was higher and the yield gain was 4 % over conventional tillage. Rice and wheat responded to 50% increased fertilizer rate over the recommended dose.